Maintenance-State Assessment Model for Building Maintenance Forecasting - Kelachi Kejeh; Ify L. Nwaogazie; Sule Samuel (Archives of Current Research International, 2022)
This study aims to provide maintenance-state assessment model for forecasting of building maintenance condition. The selected institutions for the study were state funded hospitals and schools (14 functional out of 23 general hospitals and 2 out of 3 tertiary schools). In this study, considering the shortcomings of the most widely accepted condition survey protocol (CSP) 1 matrix, that is suitable for small projects and defect based, the study developed a model that is suitable for large projects and maintenance management system based for assessment of building’s condition. This model was developed analogous to CSP 1 matrix. Two types of ratings used are condition assessment and priority assessment. These two assessment criteria are then multiplied to determine the building maintenance rating score (BMRS). The study developed a 3x3 maintenance matrix model for evaluating building maintenance-state. It also found 25% of the buildings in “good condition” requiring only planned maintenance; 68.75% in “fair condition” requiring condition monitoring and 6.25% in “serious attention” condition.